Why My Horse Doesn't Listen : Learn to Communicate Effectively - Mehrotra, Vivek (New Delhi Viva Books, 2009)
This book will help you to get your message across clearly,Whether you are communcicating with someone in person or making a presntation.
Keywords: Business Communication -- Interpersonal Communication